Konsepsi Dasar Kepribadian Islam - Abdul Mujib (‎‎‎TAZKIYA Journal of Psychology, 2003)
Personality is a term that comes from the Latin word "persona" which means "mask", or also from the Latin word "personare" which means to sound through. Meanwhile, in Arabic, personality is called syakhshiyah. In Arabic lexicology, the term nafsiyah is also known which comes from the word nafs; iniyah (aniyah) from the word ana, and the term khuluqiyah or "akhlaq" which is more widely used in classical Islamic literature. These words are similar to the word syakhshiyah, but are unique. Therefore, this research will discuss personality concepts from an Islamic perspective.